#TITLE_ALTERNATIVE# - NOFRIYALDI NIM: 20714311, ALI
Black tea (Camellia sinensis) has various activities such as antioxidant, tyrosinase, and xanthine oxidase enzyme inhibitor. Nanosuspension of a extract are known to be able to improve pharmacology activity. In this study, the effect of particle size reduction of black tea powder and extract on antioxidant activity, inhibition of tyrosinase enzyme, and inhibition of xanthine oxidase enzyme were investigated. The particle size of black tea powder was reduced by ball milling. Black tea extraction was accomplished by maceration method using ethyl acetate. Particle size reduction of black tea extract was done by precipitation technique. Evaluation of nanosuspension consisted of particle size distribution, morphology, physical stability, redispersibility and activity as antioxidant, inhibitor of tyrosinase and xanthine oxidase enzymes. The particle size of 1% nanosuspension black tea powder was 248 nm, while the particle size of nanosuspension extract with concentration of 0,5% was 173 nm. The result of physical stability showed that nanosuspension powder and nanosuspension extract were stable until 30 days. The IC50 values DPPH scavenging activity of black tea powder, nanosuspension powder, black tea extract, nanosuspension of black tea extract were 131.2 Ã‚Â± 2.56 μg/ml; 57.2 Ã‚Â± 0.41 μg/ml; 51.9 Ã‚Â± 0.71 μg/ml; 53, 2 Ã‚Â± 0.06 μg/ml, respectively. The IC50 values of tyrosinase inhibitory activity of black tea powder, nanosuspension powder, black tea extract, nanosuspension of black tea extract were 202.0 Ã‚Â± 2.01 μg/ml; 99.4 Ã‚Â± 0.28 μg/ml; 260.7 Ã‚Â± 8.76 μg/ml; 242.2 Ã‚Â± 1.21 μg/ml, respectively. The IC50 values of xantine oxidase inhibitory activity of black tea powder, nanosuspension powder, black tea extract, nanosuspension of black tea extract were 332.2 Ã‚Â± 5.72 μg/ml; 134.8 Ã‚Â± 0.72 μg/ml; 140.8 Ã‚Â± 8.01 μg/ml; 34.8 Ã‚Â± 0.17 μg/ml, respectively. Preparation of powdered nanosuspension improved all activities, meanwhile nanosuspension of ethyl acetate extract of black tea only increased the inhibition activity of tyrosinase and xanthin oxidase enzyme, but no effect on antioxidant activity.